2020
DOI: 10.3847/1538-4357/ab8799
|View full text |Cite
|
Sign up to set email alerts
|

The Late-time Afterglow Evolution of Long Gamma-Ray Bursts GRB 160625B and GRB 160509A

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 77 publications
2
9
0
Order By: Relevance
“…Using radio observations at ∼12.7 days (Ho et al 2020c), for the case where ν m < ν radio < ν c < ν X−rays we find that ν c ∼ 6.3 × 10 16 Hz for p = 2 (see Fig. 4), which is consistent with the behavior observed for GRB afterglows at late times (see, e.g., Kangas et al 2020) and it is also consistent with the radio SED presented in Fig. 5 in Ho et al (2020c).…”
Section: Discussionsupporting
confidence: 87%
“…Using radio observations at ∼12.7 days (Ho et al 2020c), for the case where ν m < ν radio < ν c < ν X−rays we find that ν c ∼ 6.3 × 10 16 Hz for p = 2 (see Fig. 4), which is consistent with the behavior observed for GRB afterglows at late times (see, e.g., Kangas et al 2020) and it is also consistent with the radio SED presented in Fig. 5 in Ho et al (2020c).…”
Section: Discussionsupporting
confidence: 87%
“…Because of the short delay between the detection and the observations, a possible contamination of the afterglow cannot be excluded. Kangas et al (2020) showed that the remaining afterglow at 35.3 days is very weak (H F160W = 26.07 mag) compared to the host galaxy. We conclude (for this object) that the HST observations considered are not strongly affected by the GRB afterglow and that the host galaxy is assumed dominant.…”
Section: Sample Selectionmentioning
confidence: 99%
“…An interesting result is found towards the end of the light curve. After removing the potential constant component, the combination of a late break and an early shallow decay makes the afterglow of this burst the most luminous ever detected for a certain time span, before the shallower post-break decay of the afterglow of GRB 160625B (which itself had a very late jet break, Kangas et al 2020) makes the latter the most luminous known at very late times again (Kann et al 2022c, in prep.). This provides further evidence for the extremely energetic nature of GRB 210905A.…”
Section: The Optical/nir Afterglow In Contextmentioning
confidence: 99%